Moral Distress in the Health Professions (Springer International Publishing, 2018)
This is the first book on the market or within academia dedicated solely to moral distress among health professionals. It aims to bring conceptual clarity about moral distress and distinguish it from related concepts. Explicit attention is given to the voices and experiences of health care professionals from multiple disciplines and many parts of the world. Contributors explain the evolution of the concept of moral distress, sources of moral distress including those that arise at the unit/team and organization/system level, and possible solutions to address moral distress at every level. A liberal use of case studies will make the phenomenon palpable to readers. This volume provides information not only for academia and educational initiatives, but also for practitioners and the research community, and will serve as a professional resource for courses in health professional schools, bioethics, and business, as well as in the hospital wards, intensive care units, long-term care facilities, hospice, and ambulatory practice sites in which moral distress originates.